Influence of the H2 proportion on NH3/H2/air combustion in hot and low-oxygen coflows - Wang, Guochang; Liu, Xiangtao; Li, Pengfei; Shi, Guodong; Si, Jicang; Liu, Zhaohui; Mi, Jianchun (International journal of hydrogen energy, 2024)
This study investigated the effect of the H2 fraction on reaction dynamics and NOx formation in a premixed NH3/H2/air jet flame within a hot coflow (JHC) through numerical simulations. We found that even a small mole fraction of H2 (e.g., XH2, F = 5%) significantly enhances the ignition of the premixed NH3/air flame. However, the presence of H2 markedly intensifies the main combustion reactions only when XH2, F ≥ 30%, resulting in a sharp increase in temperature and heat release rate. Moreover, as XH2, F increases, the NOx emission first increases until XH2, F = 75% and then decreases. Without any H2 addition, a high emission of unburned NH3 occurs in the pure NH3 JHC flame. On the other hand, when XH2, F ≥ 50%, the emissions of unburned H2 and OH increase rapidly due to extremely high temperatures. Notably, maintaining XH2, F between 5% and 20% minimizes the emissions of NOx, NH3, H2, and OH. Furthermore, the preferential diffusion of H2 plays a key role in enhancing the production of active radicals (OH, O, and H), thereby significantly boosting the initiation and combustion reactions of NH3/H2 blended fuel. [Display omitted] •Effect of H2 addition on the premixed NH3/H2/air jet flames is investigated.•A small amount of H2 (5%) in the fuel notably enhances the ignition of NH3 flame.•H2 significantly boosts major combustion reactions only when its proportion ≥30%.•Optimal H2 proportion is 5%–20% to reduce emissions of NOx, unburned NH3 and H2.•Preferential diffusion of H2 greatly enhances the ignition and combustion reactions.